Application of Donabedian quality-of-care framework to assess quality of neonatal resuscitation, its outcome, and associated factors among resuscitated newborns at public hospitals of East Wollega zone, Oromia, Western Ethiopia, 2021 - Nuredin Mohammed Guta (BMC Pediatrics, 2022)
Abstract Background Globally more than 650,000 newborns died on their first day of life from birth asphyxia. The outcome of an asphyxiated newborn depends on the quality of care they received at birth. However, the quality of care newborns received at birth may be below the WHO resuscitation standard. The reason for the poor quality of care is unclear. The Donabedian model, according to the World Health Organization (WHO), is an appropriate framework for health care assessment that focuses on improving the quality of care. So this study aims to assess the quality of neonatal resuscitation, outcome, and its associated factors among newborns with birth asphyxia at public hospitals in the East Wollega zone, 2021. Methods An institution-based cross-sectional study was conducted to observe 410 asphyxiated newborns using consecutive sampling methods. Data was gathered using a pretested structured questionnaire and checklist. Epi-data version 3.1 was used to enter data, which was subsequently exported to Statistical Package for Social Sciences version 25 for analysis. A logistic regression model was employed to determine the variables associated with the outcome variable. The adjusted odds ratio with a 95% confidence interval was calculated, and all variables associated with the outcome variable with a p-value less than 0.05 in multivariable analysis were determined to be significant factors for the outcome of resuscitated newborns. Result A total of 410 asphyxiated newborns were included in this study with a response rate of 97%. From this 87.6% of resuscitated newborns survived. Keeping baby warm [AOR = 6.9; CI (3.1, 15.6)] is associated significantly with increased chances of survival while meconium presence in the airway [AOR = 0.26; CI (0.1, 0.6)], prematurity [AOR = 0.24; CI (0.12, 0.48)], and presence of cord prolapse [AOR = 0.08; CI (0.03, 0.19)] were factors significantly associated with decreased survival of resuscitated newborns at 1 h of life. Conclusion Newborns who were kept warm were more likely to survive compared to their counterparts. While the presence of meconium in the airway, preterm, and cord prolapse was associated with the decreased survival status of newborns. Facilitating referral linkage in the event of cord prolapse, counseling on early antenatal care initiation to decrease adverse outcomes (prematurity), and neonatal resuscitation refresher training is strongly recommended.